2018
DOI: 10.3390/met8070549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turning and Surface Polishing Treatments on Surface Integrity and Fatigue Performance of Nickel-Based Alloy GH4169

Abstract: In this paper, the effects of turning and surface polishing treatments on surface integrity and fatigue properties of superalloy GH4169 were investigated. Finish turning (FT), surface circumferential polishing treatment (TCP), surface oblique texture (TCPO), and surface axial texture (TCPA) were applied to GH4169 superalloy. The surface roughness, surface topography, residual stress, microhardness, and microstructure after different processes were studied. Rotating bending fatigue tests were carried out to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Recently, the machining of nickel-based alloy GH4169 faces great challenges primarily related to cutting forces and cutting temperatures [9]. These issues significantly impact the machining process in terms of efficiency and quality [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the machining of nickel-based alloy GH4169 faces great challenges primarily related to cutting forces and cutting temperatures [9]. These issues significantly impact the machining process in terms of efficiency and quality [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 For this purpose, vast literature is dedicated to the selection of the most suitable process parameters able to optimize the static 21 and the fatigue strength. 17,21,22 To this regard, the design of components that undergo cyclic loads should be carefully considered, as prediction of fatigue life and industrial safety depends on many different factors, such as loading conditions, the manufacturing processes of the starting materials, 23 the crystalline structure of the component, 24 the finishing condition, 25,26 and the presence of defects. As an example, the presence of interstitial elements or non-metallic inclusions in the base materials to be welded can represent preferential crack initiation sites during cyclic loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al [11] found that micro-cracks formed on the surface of AISI 4340 steel during shot peening would have an impact on the initiation location of cracks. Wu et al [12] studied the influence of different polishing methods on the rotary bending fatigue life of nickel-based Alloy GH4169. Klein et al [13] showed that the surface morphology had a significant impact on the cyclic deformation behavior of TWIP steel under high cycle fatigue.…”
Section: Introductionmentioning
confidence: 99%